Legal Protection for Consumer of the Unlicensed Vapor from Drug and Food Supervisory Agency - Dedhi Bima Samudra; Noor Fatimah Mediawati; M Tanzil Multazam; Emy Rosna Wati (Universitas Lampung, 2017)
This research begins with the number of liquid vapor which spread in Indonesia that is not licensed by BPOM, and there is no clear law for liquid vapor, so there is no clarity from legal protection against liquid vapor consumers who are not licensed by BPOM. Therefore, in this research, the formulation of the problem is as follows: Is there legal protection against liquid vapor consumers who are not licensed by BPOM? The purpose of this research is to determine whether there is legal protection against liquid vapor consumers who are not licensed by BPOM. So this research can be useful for subsequent research that has the same theme and beneficial to researchers, liquid vapor consumers and also for the government. The research method used is the normative method. Normative research methods use the statute approach. The result of the research shows that there is a legal protection for liquid vapor consumer who is not licensed by BPOM, which is reviewed from the Law of the Republic of Indonesia Number 36 Year on concerning the health of Article 113 paragraph (1) and Article 114, Law of the Republic of Indonesia Number 8 Year 1999 on Consumer protection Article 8 paragraph (1) c and paragraph (1) i, Regulation of the Head of the Food and Drug Supervisory Agency of the Republic of Indonesia Number 4 Year 2017 on the Supervision of the Importation of Drugs into the Territory of Indonesia Article 4 paragraph (1). Keywords: Legal Protection, Consumer, Liquid-Vapor